2020
DOI: 10.1039/c9fo02097g
|View full text |Cite
|
Sign up to set email alerts
|

Lysine blockage of milk proteins in infant formula impairs overall protein digestibility and peptide release

Abstract: High levels of blocked lysine in infant formula lead to increasing average peptide length after in vitro digestion in infants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(25 citation statements)
references
References 41 publications
1
21
0
Order By: Relevance
“…14 It is now acknowledged that the milk protein structures can influence nutrient bioavailability, rates of absorption and postprandial outcomes. [15][16][17][18][19] Milk protein structure can be altered by processing such as heat treatment, partly due to whey protein denaturation and aggregation. However, so far, only a few studies 20,21 have directly linked these heat-induced protein structures to protein digestion kinetics, and even less in the context of IMFs.…”
Section: Introductionmentioning
confidence: 99%
“…14 It is now acknowledged that the milk protein structures can influence nutrient bioavailability, rates of absorption and postprandial outcomes. [15][16][17][18][19] Milk protein structure can be altered by processing such as heat treatment, partly due to whey protein denaturation and aggregation. However, so far, only a few studies 20,21 have directly linked these heat-induced protein structures to protein digestion kinetics, and even less in the context of IMFs.…”
Section: Introductionmentioning
confidence: 99%
“…It was indeed experimentally validated that lysine modification impairs susceptibility of proteins to enzymatic digestion (reviewed in [ 173 , 183 , 184 , 185 , 186 , 187 , 188 , 189 ]). Various mechanisms to explain impaired digestion have been suggested, including direct protection of lysine as a proteolytic target site, prevention of docking of proteolytic enzymes as a result of a modified lysine residue located immediately adjacent to an intended cleavage site, or by means of cross-linking with target residues [ 190 ].…”
Section: Relation Between β-Lactoglobulin Fold and Digestion And Tmentioning
confidence: 99%
“…Whereas, unfolding prior to aggregation in the presence and absence of reducing sugars can facilitate enzymatic hydrolysis, it has been shown that high levels of glycation in infant formula results in impaired digestibility. [ 22 ] Thus, exploring the molecular mechanisms of interaction between heat‐treated BLG, as a potential antigen present in infant nutrition, and the human APCs is of particular interest. The aim of the present study was first to evaluate and compare heat and glycation induced changes in immunoreactivity of BLG.…”
Section: Introductionmentioning
confidence: 99%